2010
DOI: 10.2485/jhtb.19.187
|View full text |Cite
|
Sign up to set email alerts
|

Dual Nature of TGF-β1 in Osteoblastic Differentiation of Human Periodontal Ligament Cells

Abstract: This study investigated the effect of various treatments with TGF-β1 in osteogenic differentiation of human periodontal ligament (HPDL) cells.HPDL cells were treated with single 1 ng/ml, 100 ng/ml or multiple (12-h intervals) 1 ng/ml TGF-β1. Alkaline phosphatase (ALP) activity was detected by ALP activity staining at 4 days. Phospho-Smad3 was detected by western blotting and transcription of osteogenic differentiation markers (RUNX2, ALPL, IBSP: bone sialoprotein, BGLAP: osteocalcin) were determined by real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…1B and C), similar to repeated TGF-β1 administration, as we previously reported 4) . Expressions of other osteoblast markers and differentiation-related genes such as BSP, IGF-1, RUNX2, and MSX2 are also decreased following repeated Wnt3A administration ( Fig.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…1B and C), similar to repeated TGF-β1 administration, as we previously reported 4) . Expressions of other osteoblast markers and differentiation-related genes such as BSP, IGF-1, RUNX2, and MSX2 are also decreased following repeated Wnt3A administration ( Fig.…”
Section: Discussionsupporting
confidence: 71%
“…First, repeated Wnt3A treatment downregulates ALP expression and early-phase osteoblast differentiation of HPDL cells. Previously, we reported that repeated TGF-β1 treatment to HPDL cells downregulates ALP expression 4) . We observed subsequent decreased IGF-1 expression and inhibition of PI3K/Akt signaling 3) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous and overexpressed IGF-1 recovered ALP activity and mRNA expression of osteoblast differentiation marker genes even with repeated TGF-1 administration. Thus, IGF-1 plays a central role of osteoblast differentiation 13) . BMP-2, an agent that enhances osteoblast differentiation and function, increases IGF-1 synthesis in osteoblasts 26) .…”
Section: Expression Of Igf-1 and P-akt Proteinmentioning
confidence: 99%
“…TGF-1 increases mRNA levels of osteoblast differentiation markers and alkaline phosphatase (ALP) activity in murine bone marrow stromal cells 11) . However, TGF-1 also blocks osteogenesis by various mechanisms depending on its concentration, the cell density, and differentiation stage of the cells 13) . Some studies reported that TGF-1 has biphasic and concentration-dependent effects on osteoblast differentiation [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%